ANTIBACTERIAL AND ANTIFUNGAL ACTIVITY OF SOLID SOAP ESSENTIAL OIL OF NUTMEG SEEDS (Myristica fragrans H.) ON Propionibacterium acnes AND Candida albicans. - -, Herlyana; Riyanti, Tiara; Rahman, Ika Ristia; Kurnianto, Erwan (Journal Pharmacy Of Tanjungpura, 2024)
Nutmeg is most often used as a spice and essential oil. Nutmeg seed essential oil is widely geared towards diseases caused by bacteria or fungi. The essential oil content of nutmeg seeds consists of myristic acid, trimyristin, and glycerides from lauric, stearic, and palmitic acids, which have activities as anti-oxidants, anticonvulsants, analgesics, anti-inflammation, anti-diabetes, antifungal and antibacterial. Propionibacterium acnes is a bacterium that plays an important role in the development of acne, and Candida albicans is the fungus that most often causes skin infections. The purpose of this study was to determine whether solid soap from the essential oil of nutmeg seeds as antibacterial and antifungal activity against the growth of Propionibacterium acnes and Candida albicans and what is the diameter of the inhibitory zone. This test uses the disc disc method with variations in the concentration of NaOH in solid soap. The concentration of NaOH in F1 is 45.21 g, F2 is 40.45 g, F3 is 35.7 g. The results of the inhibitory zone of Propionibacterium acnes at F1 of 16.67 mm, F2 of 13.421 mm, F3 of 17.91 mm, and in Candida albicans at F1 of 24.608 mm, F2 of 24.476 mm, F3 of 25.394 mm. This indicates that each formulation has antibacterial and antimicrobial activity.